Endocrine disruptor DDE associated with a high-fat diet enhances the impairment of liver fatty acid composition in rats - Rodríguez-Alcalá, Luis M. (2016)
The banned pesticide dichlorodiphenyltrichloroethane (DDT) and its main metabolite, p,p′-dichlorodiphenyldichloroethylene (DDE), are commonly found in the food chain and in all tissues of living organisms. DDE is associated with metabolic diseases acting as an endocrine disruptor and more recently with the obesity pandemic. This study focuses on using fatty acid analysis to relate DDE exposure and metabolic dysfunction: liver and adipose tissue (visceral and subcutaneous) composition from male Wistar rats fed a standard (STD) or high-fat (HF) diet versus the addition of DDE in water. DDE exposure increased liver levels of palmitic, stearic, oleic, trans fatty, and linoleic acids having altered the n6 and n3 pathways leading to high concentrations of arachidonic acid and DHA (C22:6 n3). The results of this study confirm the close relationship between this pesticide metabolite and hepatic lipid dysfunction, underscoring its role as an emerging target for the prevention and therapy of nonalcoholic fatty liver disease (NAFLD).